Activities and perceived risk of transmission and spread of sars-cov-2 among specialists and residents in a third level university hospital in Spain - Aranaz Andrés, Jesús María; McGee-Laso, Amaranta; Galán, Juan Carlos; Cantón, Rafael; Mira, José (International journal of environmental research and public health, 2021)
This study aims to identify factors related with SARS-CoV-2 infection in physicians and internal residents during the SARS-CoV-2 pandemic at a tertiary hospital in Spain, through a cross-sectional descriptive perception study with analytical components through two questionnaires directed at professionals working at the Ramon y Cajal University Hospital between February and April 2020. In total, 167 professionals formed the study group, and 156 professionals comprised the comparison group. Seventy percent of the professionals perceived a shortage of personal protective equipment (PPE), while 40% perceived a shortage of hand sanitiser, although more than 70% said they used it properly. Soap was more available and had a higher percentage of correct use (73.6–79.5%) (p > 0.05). Hand hygiene was optimal in >70% of professionals according to all five WHO measurements. In the adjusted model (OR; CI95%), belonging to a high-risk specialty (4.45; 1.66–11.91) and the use of public transportation (3.27; 1.87–5.73) remained risk factors. Protective factors were changes of uniform (0.53; 0.32–0.90), sanitation of personal objects before the workday (0.55; 0.31–0.97), and the disinfection of shared material (0.34; 0.19–0.58). We cannot confirm that a shortage or misuse of PPE is a factor in the spread of SARS-CoV-2. Fears and assessments are similar in both groups, but we cannot causally relate them to the spread of infection. The perception of the area of risk is different in both groups, suggesting that more information and education for healthcare workers is needed.
Keywords: COVID-19; healthcare workers; perceived risk; risk of transmission; SARS-CoV-2; Scopus; WOS(2)